Contextual Islamic Religious Education at the Primary School Level: Integrating the Banjar Life Philosophy into the IRE Curriculum - Moh. Ali Muttaqo; Normuslim Normuslim; Hamdanah Hamdanah (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: Islamic Religious Education (IRE) at the Primary School Level in multicultural societies such as Indonesia must evolve to remain relevant and impactful. One way to achieve this is by contextualizing IRE at the Primary School Level by integrating local cultural values. This study explores how the philosophical values of the Banjar ethnic group—such as baiman (faith), batakwa (piety), and basusila (morality)—can be effectively integrated into the IRE at the Primary School Level curriculum to enhance students' moral and character development. Aim: The objective is to identify and analyze strategies for embedding these local values into religious education while evaluating their influence on learners' moral behavior. Method: A qualitative descriptive approach was employed, utilizing thematic analysis and library research as the primary methods. Data were collected through document analysis, literature review, and secondary reports involving educational institutions in South Kalimantan. Result and Discussions: The findings show that integrating Banjar cultural values—such as cooperation (gotong-royong) and mutual respect—into IRE at the Primary School Level not only enhances the contextual relevance of the curriculum but also reinforces students' religious identity and social awareness. Results indicate that 75% of students better understood Islamic values when taught through culturally familiar practices. In comparison, 80% of respondents acknowledged a positive transformation in their character and discipline through contextual religious instruction. Discussion revealed that such integration supports a holistic educational approach, linking cultural identity with moral development. It also addresses gaps in conventional curricula by offering inclusive, place-based learning models. In conclusion, this study affirms the significant role of local wisdom in shaping ethical and religious values in education. It recommends systematic curriculum development, teacher training, and community collaboration to sustain culturally responsive IRE at the Primary School Level. Integrating Banjar values into religious instruction fosters academic understanding, stronger moral integrity, and cultural rootedness among students.